The clinical and electron microscopic evaluation of the impact of pulsed dye laser techniques on solar lentigines (randomized clinical trial). (2nd January 2022) - Abd.El-Naby, Naeim; Mostafa Ali, Mai; Hawwam, Soha Abdalla; Sarhan, Naglaa
Abstract: Background: Solar lentigines are skin lesions manifested by benign dark pigmentation causing a cosmetic problem in many patients. Several treatment modalities used for the management of solar lentigines. Side effects and rates of recurrence may be associated with them. Objective: Treating solar lentigines with two different techniques of pulsed dye laser (PDL) and evaluation of the results both clinically and via the examination of ultrastructural changes by electron microscopy. Patients and methods: This study was conducted on 22 subjects with solar lentigines and having Fitzpatrick III–IV skin types, was managed by the use of PDL after enrolling them into two groups. Group I (one stacked PDL was used) and Group II (treated by stacked PDL in two sessions, 1 month apart). At baseline and 6 months after treatment, two punch biopsies with a diameter of 2 mm were taken from all patients. All taken biopsies were prepared for light and electron microscopic examinations. Results: Both PDL techniques induced significant better clinical and histological outcomes. No one demonstrated any postoperative complications such as post-inflammatory hyperpigmentation and scarring. Conclusions: The two techniques of PDL are efficient for solar lentigines treatment.